2018
DOI: 10.1007/s40279-018-0964-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Balance Training on Balance Performance and Functional Outcome Measures Following Total Knee Arthroplasty: A Systematic Review and Meta-Analysis

Abstract: Balance training improved walking capacity, balance-specific performance and functional outcome measures for elderly individuals following TKA. These findings may improve clinical decision-making for appropriate post-TKA exercise prescription to minimise falls risks and optimise physical function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Current meta-analysis performed publication bias, subgroup analysis, and subgroup analysis for overall function. Doma et al [22] indicated that balance training improved walking capacity, balance-specific performance, and functional outcome measures for elderly individuals following total knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Current meta-analysis performed publication bias, subgroup analysis, and subgroup analysis for overall function. Doma et al [22] indicated that balance training improved walking capacity, balance-specific performance, and functional outcome measures for elderly individuals following total knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis carried out a subgroup analysis and assessed the risk of publication bias for all the studies. Doma et al [ 24 ] reported that balance training enhanced functional outcome measures, balance-specific performance, and walking capacity for elderly people who underwent overall knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…strengthening exercises [ 22 ], sensori-motor training (e.g. integration of proprioceptive inputs on balance and gait) [ 13 , 30 , 48 ] or electromyostimulation training [ 20 ]. The strengthening exercises were performed underloaded (coordination at 10–20% of 1-Repetition Maximum (1RM)) or at submaximal intensity (strength endurance at 30–50% of 1RM and hypertrophy at 50–80% of 1RM) and targeted muscles of the lower extremities (e.g.…”
Section: Methodsmentioning
confidence: 99%